SOLUTION-PROCESSED SNO2 ELECTRON TRANSPORT LAYER: ADVANCEMENT IN FLEXIBLE PRINTED PEROVSKITE SOLAR CELLS - Kiani, Muhammad Salman (Nazarbayev University School of Sciences and Humanities, 2024)
The burgeoning field of flexible and printed perovskite solar cells (PSCs) presents a promising future for renewable energy applications, especially in wearable electronics and smart infrastructure. Realizing their potential hinges on developing functional layers processed at low temperatures. Due to its favorable properties, tin oxide (SnO2) has emerged as a potential material for the electron transport layer (ETL). This study delves into synthesizing and utilizing SnO2 quantum dots (QDs) for ETL fabrication in flexible and printed PSCs. SnO2 QDs are synthesized via a solvothermal method and formulated into aqueous and printable ETL ink solutions with varying QD concentrations. The electrical conductivity of the resultant ETL films largely depends on the concentration of SnO2 QDs in the ETL inks. A compact layer of SnO2 QD-based ETL can facilitate effective electron transfer from the perovskite layer to the transparent conducting oxide (TCO) layer in PSCs. Achieving an ideal thickness of SnO2 QD-based ETL can reduce charge recombination losses and increase charge extraction efficiency in PSCs, thus improving the overall performance of devices. PSCs are fabricated on flexible plastic substrates using the slot-die coating technique. Notably, ETLs fabricated using 2 wt.% SnO2 QD inks exhibit superior performance, yielding high mean power conversion efficiency (PCE) and showcasing a champion device with 10% PCE. This investigation underscores the potential of SnO2 QDs for the scalable production of PSCs. Despite the prevailing use of SnO2 nanoparticle (NP) dispersion solutions in current PSC manufacturing processes, a comparison is made between the as-synthesized SnO2 QDs-based ETL and the SnO2 NP-based ETL inks. Our findings reveal an 11% enhancement in average device performance, attributed to SnO2 QD-based ETLs’ ability to reduce trap states in the perovskite layer and facilitate charge extraction. In conclusion, this scientific work emphasizes the transformative potential of SnO2 QDs in advancing flexible and printed PSC technology. The study contributes to the fundamental understanding of PSCs and paves the way for practical applications in renewable energy generation. Continued research in this domain promises to propel the development of sustainable energy solutions and shape the future of solar technology.
Keywords: Type of access: Open